Uncommon Progression of an Extradural Spinal Meningioma - Atef Ben Nsir; Mohamed Boughamoura; Houda Mahmoudi; Mohamed Kilani; Nejib Hattab (Case Reports in Surgery)
Extradural spinal meningiomas are rare. Our understanding of purely extradural spinal meningiomas is still incomplete and they may be easily confused with malignant neoplasms, much more common in this location. We report a rare case of a purely extradural thoracic spine meningioma in a 70-year-old man, with an unusual progression. In addition we discuss the pathogenesis of these tumors and the potential pitfalls in differential diagnosis and review the relevant literature concerning their treatment and outcome.